2015
DOI: 10.1111/gbi.12155
|View full text |Cite
|
Sign up to set email alerts
|

Chromium‐isotope signatures in scleractinian corals from the Rocas Atoll, Tropical South Atlantic

Abstract: Chromium-isotope compositions (expressed as δ(53) Cr) of recent and ancient skeletal and non-skeletal carbonates are currently explored as a (paleo-) redox-proxy for shallow seawater. The idea behind this approach is that biogenic and non-biogenic carbonates could potentially be used as archives recording the Cr-isotope composition of seawater in which they formed, and with this contribute to the reconstruction of past paleo-environmental changes in the marine realm, and potentially to climate changes on land.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
67
5
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(84 citation statements)
references
References 61 publications
11
67
5
1
Order By: Relevance
“…Methods used in this study for the purification and isotope analysis of Cr in seawater samples and biogenic carbonates follow those described in Paulukat et al (2016) and Pereira et al (2015), with small modifications. Briefly, filtered and spiked seawater samples were transferred into 1 L Savillex ™ teflon beakers, evaporated, redissolved in 50 mL of aqua regia, and evaporated again.…”
Section: Ion Chromatographic Separation Of Chromiummentioning
confidence: 99%
See 3 more Smart Citations
“…Methods used in this study for the purification and isotope analysis of Cr in seawater samples and biogenic carbonates follow those described in Paulukat et al (2016) and Pereira et al (2015), with small modifications. Briefly, filtered and spiked seawater samples were transferred into 1 L Savillex ™ teflon beakers, evaporated, redissolved in 50 mL of aqua regia, and evaporated again.…”
Section: Ion Chromatographic Separation Of Chromiummentioning
confidence: 99%
“…However, investigations addressing the behavior and uptake mechanism of Cr, and the potential isotope fractionations between seawater and biogenic carbonates are scarce. All studies so far conducted on marine biogenic carbonates have revealed the incorporation of isotopically lighter chromium into skeletal and non-skeletal carbonates compared to Cr isotope signatures of seawater at the respective sampling sites (e.g., Pereira et al, 2015;Holmden et al, 2016;Farkaš et al, 2018). Due to a lack of ambient seawater δ 53 Cr data to compare the 53 Cr data of various foraminifera analyzed by Wang et al (2016), conclusion with respect to using δ 53 Cr data of foraminiferal species as a reliable proxy of seawater δ 53 Cr could not be made in the respective study.…”
Section: Shells -Chromium Isotope Compositions and Chromium Concentramentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, at Rocas Atoll, despite the existence of information on S. stellata abundance (Echeverría et al 1997, Fonseca et al 2012, percent coverage (Longo et al 2015), and its importance as a natural archive for paleoclimate studies (Mayal et al 2009, Oliveira 2012, Pereira et al 2016, there is no record of other aspects of its population dynamics. Part of the reason of the absence of population models for Brazilian coral species are due to this lack of information to produce them.…”
Section: Introductionmentioning
confidence: 99%